Prevalence of Oral Lesions in a private clinic in Goiás (2022-2025): A cross-sectional study (Research, Society and Development, 2025)
This study aims to fill a gap in the literature by investigating the prevalence of oral lesions in private clinics in Goiás, from 2022 to 2025. The cross-sectional study analyzed the prevalence of oral lesions in patients treated at a private clinic in Goiás, between 2022 and 2025, with the aim of identifying regional patterns and associated factors. The sample included 638 patients, predominantly female (61.4%), with a mean age of 48.96 years. Among the most prevalent lesions were fibrous hyperplasia, burning mouth syndrome, and lichen planus. It was observed that women over 40 years of age were more predisposed to these conditions, while the use of dentures was a significant risk factor for inflammatory lesions in individuals over 50 years of age. The study also revealed that behavioral factors contributed to the occurrence of periapical cysts and pyogenic granulomas, more frequent in men. The results emphasize the need for personalized preventive interventions and educational campaigns targeting denture users and specific demographic groups. Furthermore, the data can support regional public policies that integrate preventive and educational strategies in the context of oral health in private clinics. Despite limitations, such as the use of retrospective data and the exclusion of public services, this work provides new and relevant information to the dental literature.